MALAY-BULUNGAN LANGUAGE PREFIXATION (BMB) IN THE COMMUNITY IN NORTH KALIMANTAN, BULUNGAN REGENCY - Marlian Marlian; Nurhadi Nurhadi; Esti Swastika Sari (Sean Institute, 2023)
The Malay-Bulungan (BMB) language is unique, especially in the field of morphology. This study aims to determine the prefix and its application in Malay-Bulungan (BMB). This research was conducted using a generative morphology study with a model developed by Halle, namely the IP model (Item and Process), with data derived from interviews and observations of native speakers. The results of this study indicate that in the Malay-Bulungan (BMB) language, there is a derivation process in the use of the prefix